PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA PUSKESMAS RANTAU BADAUH KABUPATEN BARITO KUALA - Muhammad Fahmi (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
Abstract: This Research aims to understand about the simultant and partial influence of the services quality which consists of reliability, responsiveness, assurance, emphaty and tangible in against community satisfaction at Health Center of Rantau Badauh Kabupaten Barito The Population of these research are the people who sought services At Health Center of Rantau Badauh Kabupaten Barito Kuala who totaled more than 5.000. While the sample is only 100 people. The instruments that use to collect data are through questionnaires and hypothesis testing which is done by using validity test, reliability test, classic assumption test, multiple linear regression analysis, t-test, f-test, through the help of SPSS version 17. It is concluded that the Quality of service consisting of variable reliability, responsiveness, assurance, emphaty and tangible simultaneously and partially has significant effect on people’s satisfaction at Health Center of Rantau Badauh Barito Kuala with emphatic variable has the dominant influence. Keywords: Reliability, Responsiveness, Assurance, Emphaty, Tangible, Performance Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh kualitas pelayanan yang terdiri dari variabel reliability, responsiveness, assurance, emphaty dan tangible secara simultan maupun parsial terhadap kepuasan masyarakat pada Puskesmas Rantau Badauh Kabupaten Barito Kuala. Populasi dalam penelitian ini adalah seluruh masyarakat yang pernah meminta pelayanan pada Puskesmas Rantau Badauh Kabupaten Barito Kuala yang berjumlah lebih dari 5.000 orang, sedangkan sampel yang di ambil sebanyak 100 orang. Instrument pengumpulan data kuesioner dan uji hipotesis dilakukan dengan uji validitas, reliabilitas, uji asumsi klasik, analisis regresi linear berganda, uji t, uji f melalui bantuan program SPSS versi 17. Kesimpulan penelitian ini adalah variabel reliability, responsiveness, assurance, emphaty dan tangible secara simultan maupun parsial berpengaruh signifikan terhadap kepuasan masyarakat pada Puskesmas Rantau Badauh Kabupaten Barito Kuala dengan variabel Emphaty sebagai variabel yang berpengaruh dominan Kata kunci : Reliability, Responsiveness, Assurance, Emphaty, Tangible, Kinerja